Effect of prebonding anneal on the microstructure evolution and Cu–Cu diffusion bonding quality for three-dimensional integration - Peng, L. (2013)
Electroplated copper (Cu) films are often annealed during back-end processes to stabilize grain growth in order to improve their electrical properties. The effect of prebonding anneal and hence the effective initial grain size of the Cu films on the final bond quality are studied using a 300-nm-thick Cu film that was deposited on a 200-mm silicon (Si) wafer and bonded at 300°C. As compared with the control wafer pair with a prebonding anneal at 300°C for 1 h in N2, the wafer pair without a prebonding anneal showed greater improvement in void density based on c-mode scanning acoustic microscopy (c-SAM). Dicing yield and shear strength were also enhanced when a prebonding anneal was not applied. This improvement is due to substantial grain growth of smaller Cu grains during the bonding process, which leads to a stronger Cu–Cu bond. Our work has identified a Cu–Cu bonding process with a lower total thermal budget, which is seen as a favorable option for future three-dimensional (3D) integrated circuit (IC) technology.